2017
DOI: 10.1021/acs.jmedchem.6b01761
|View full text |Cite
|
Sign up to set email alerts
|

Drug Discovery Targeting Bromodomain-Containing Protein 4

Abstract: BRD4, the most extensively studied member of the BET family, is an epigenetic regulator that localizes to DNA via binding to acetylated histones and controls the expression of therapeutically important gene regulatory networks through the recruitment of transcription factors to form mediator complexes, phosphorylating RNA polymerase II, and by its intrinsic histone acetyltransferase activity. Disrupting the protein–protein interactions between BRD4 and acetyl-lysine has been shown to effectively block cell pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
329
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 256 publications
(332 citation statements)
references
References 177 publications
(388 reference statements)
2
329
0
1
Order By: Relevance
“…Despite significant effort invested in the development of small molecule BRD4 inhibitors, none have been yet reported that are highly selective for BRD4 over other members of the BET family (Liu et al, 2017). To this end, by utilizing a structure-based drug design for the KAc binding pocket, ZL-0420 and ZL-0454, containing a dihydroquinolin-2(1 H )-one or N -cyclopentyl-benzenesulfonamide binding tail, were synthesized.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite significant effort invested in the development of small molecule BRD4 inhibitors, none have been yet reported that are highly selective for BRD4 over other members of the BET family (Liu et al, 2017). To this end, by utilizing a structure-based drug design for the KAc binding pocket, ZL-0420 and ZL-0454, containing a dihydroquinolin-2(1 H )-one or N -cyclopentyl-benzenesulfonamide binding tail, were synthesized.…”
Section: Resultsmentioning
confidence: 99%
“…Because of its diverse roles in inflammation, cancer and fibrosis, development of BRD4 inhibitors have been the subject of intense focus (Liu et al, 2017). In this study, we have applied structure-based drug design to advance the pharmacopeia of BRD4 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Fusions of BRD3/4 with the protein Nuclear in Testis give rise to NUT midline carcinoma, an aggressive malignancy, and BRD4 has been shown to occupy super-enhancer regions that drive oncogenic transcription programs in a range of cancers (21)(22)(23)(24)(25). As a consequence, BRD4 in particular has become a major target for the design of cancer therapeutics that inhibit the acetyllysine-binding properties of its bromodomains (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of new BRD4 inhibitors may provide reference for drug design and make a contribution to the treatment of cancer or other diseases. Currently, more than a dozen of BRD4 inhibitors have progressed into human clinical trials for the treatment of cancer or other diseases [38]. These molecules usually have a unique head moiety that can form critical hydrogen bonds with residues of the BRD4 binding pocket.…”
Section: Discussionmentioning
confidence: 99%